Influenza vaccination from the perspective of health care workers at university hospitals. - Dominika Rykowska; Tomasz Sobierajski; Magdalena Okarska-Napierała; Monika Wanke-Rytt; Ernest Kuchar (PLoS ONE)
Background The influenza vaccination rate of healthcare workers (HWs) in Poland is low. Before implementing methods for promoting influenza vaccination, it is crucial to identify attitudes towards vaccination. We aimed to examine the knowledge and attitudes towards influenza vaccination of HWs at university hospitals. Moreover, we evaluated the incentives for getting influenza vaccination among HWs. Methods From September 2020 to October 2020, we surveyed HWs in one children's hospital and two adults' hospitals in Warsaw (Poland). We included only fully and correctly completed surveys into final analysis. Results A total of 950 questionnaires (85% women, 45% <40 years old, 33% physicians and 48% nurses, 56% working in a children's hospital) were evaluated. Of all HWs, 25% declared they were vaccinated and 54% planned to get vaccinated in the next season. We have analyzed attitudes towards influenza vaccination and motivations to get vaccinated. Conclusions Among HWs in academic hospitals, males, people <40 years old, physicians and those working in children's hospital are more likely to get vaccinated and their attitudes towards influenza vaccination are more positive. Of those less likely to get vaccinated, people >40 years old and nurses could be effectively persuaded by free and on-site influenza vaccination. Moreover, free access to vaccination is the strongest motivator for vaccination among all HWs. The attitudes towards mandatory influenza vaccination differ sharply among HWs-while physicians are ready to accept it, nurses are not. Trial registration ClinicalTrials.gov Identifier: NCT04569019.